Tafsir Ayat Al Quran Tentang Penistaan Agama - Aszmi Farida; Randy Maulana; Akenada Putri Millian; Jendri Jendri (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2025)
Complex social problems, such as blasphemy, often arise as a result of social plurality. Time pressure can make the legal system no longer subjective in such situations. If protests continue, the punishment imposed on those deemed to have committed blasphemy will be increasingly severe. Cases of blasphemy have increased in recent times. When some people easily say that such an attitude is blasphemy, the author was moved to investigate and analyze the verses in the Qur'an related to blasphemy using their understanding of classical, medieval, and contemporary interpretations. This qualitative research uses a comparative approach. The author uses Tafsir Jami' al-Bayan'an Ta'wil ai al-Qur'an, Tafsir al-Jami' li Ahkam Al-Qur'an, and Tafsir al-Munir from Wahbah az-Zuhailîy as primary data sources, and books related to blasphemy are used as secondary data sources. The data were studied using deductive-comparative methods. This study shows that some words are involved in the discussion of blasphemy when compared to its general meaning, although the Qur'an does not mention the word "blasphemy" explicitly. This study shows that al-Qurthubîy and Wahbah az-Zuhailîy interpret behavior related to blasphemy in the same way, as does ath-Thabarîy, although ath-Thabarîy does not always mention the details of the behavior. Since the interpretations of the three are almost the same so far, these differences do not have much impact on the author's work. In terms of blasphemy, every example mentioned by the three commentators is a behavior that can be said to be fatal. Therefore, society must be careful and careful in dealing with problems, especially those related to blasphemy, so that slanderous behavior can be prevented and prevented.